FREQUENCY OF PRIMARY UTERINE MALIGNANCY IN HYSTRECTOMY SPECIMENS OF POSTMENOPAUSAL WOMEN – A STUDY OF 225 CASES AT COMBINED MILITARY HOSPITAL PESHAWAR: Uterine Malignancy - Sarfraz, Tariq; Bashir, Saima; Bashir, Jawad; Tariq, Humaira; Muhammad, Iqbal; Bashir, Hadeel (Pakistan Armed Forces Medical Journal, 2014)
Objective: To determine the frequency of primary uterine malignancy in hysterectomy specimens in women with postmenopausal bleeding. Study Design: A descriptive cross-sectional study. Place and Duration of Study: It was conducted in the department of histopathology at Combined Military Hospital, Peshawar from 1st September 2010 to 31st May 2011. Material and Methods: A total of 225 hysterectomy specimens of postmenopausal women were examined grossly and microscopically to analyse the underlying pathology. Results: The mean age of patients with malignant diseases was 56.4 years and with benign diseases 49.3 years. Out of 225 patients 215 (95.6%) were found to have benign pathologies and 10 (4.4%) had malignant lesions. The frequency and histological pattern of primary uterine malignancy was; endometrial carcinoma 3.1%, cervical carcinoma 0.9% and leiomyosarcoma 0.4%. The benign pathologies included leiomyoma 35.6%, atrophic endometritis 16.4%, endometrial hyperplasia 15.1%, adenomyosis 11.1%, endometrial polyp 10.2%, adenomyoma 6.7% and endometrial stromal nodule 0.4%. Conclusion: This study shows that frequency of malignancy in postmenopausal women is low in our set up and most of the underlying pathologies are benign. The most frequent malignancy found in postmenopausal women is endometrial carcinoma followed by cervical carcinoma.